2016
DOI: 10.1038/srep24256
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of BMP receptor type IB decreased bone mass in association with compromised osteoblastic differentiation of bone marrow mesenchymal progenitors

Abstract: We previously found that disruption of two type I BMP receptors, Bmpr1a and Acvr1, respectively, in an osteoblast-specific manner, increased bone mass in mice. BMPR1B, another BMP type I receptor, is also capable of binding to BMP ligands and transduce BMP signaling. However, little is known about the function of BMPR1B in bone. In this study, we investigated the bone phenotype in Bmpr1b null mice and the impacts of loss of Bmpr1b on osteoblasts and osteoclasts. We found that deletion of Bmpr1b resulted in ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 44 publications
0
29
0
1
Order By: Relevance
“…However, at 8 weeks of age, we observed the increased trabecular bone phenotype only in female in Srgap2‐cKO mice. Sex‐restricted phenotypes in genetic mouse models are not uncommon . Skeletal sexual dimorphism depends not only on androgen action in males and estrogen action in females, but also on complex sex‐specific and time‐specific interactions between sex hormones, the growth hormone/insulin‐like growth factor‐1 (GH/IGF‐1) axis, and mechanical loading.…”
Section: Discussionmentioning
confidence: 99%
“…However, at 8 weeks of age, we observed the increased trabecular bone phenotype only in female in Srgap2‐cKO mice. Sex‐restricted phenotypes in genetic mouse models are not uncommon . Skeletal sexual dimorphism depends not only on androgen action in males and estrogen action in females, but also on complex sex‐specific and time‐specific interactions between sex hormones, the growth hormone/insulin‐like growth factor‐1 (GH/IGF‐1) axis, and mechanical loading.…”
Section: Discussionmentioning
confidence: 99%
“…Mice genetically engineered to overexpress epidermal growth factor receptor ligand amphiregulin (AREG) demonstrate greater femoral BMD and total bone in the metaphyseal region at 4 and 8 weeks of age compared with WT controls, but after 10 weeks of age, there is no difference between the genotypes anymore . In addition, Shi and colleagues identified that deletion of BMP receptor BMPR1B resulted in trabecular bone loss at 8 weeks of age, which was not found either just after birth or at 11 weeks of age . Our lab also previously reported a temporal difference in skeletal changes with age between trabecular and cortical bone in DNA repair–deficient female trichothiodystrophy (TTD) mice where these mice show accelerated bone aging after 39 weeks of age .…”
Section: Discussionmentioning
confidence: 66%
“…5). Our in vitro cellular mechanistic studies further indicated that haploinsufficiency or even the knockout of Bmpr1b did not apparently affect cellular response to BMP ligands (Shi et al, 2016). Consistent with this, we observed that homozygous knockout of Bmpr1b did not rescue skull deformities (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 81%